Frequent Infection of Cortical Neurons by JC Virus in Patients With Progressive Multifocal Leukoencephalopathy - Wüthrich, Christian; Koralnik, Igor J. (Journal of neuropathology and experimental neurology, 2012)
ABSTRACTThe human polyomavirus JC (JCV) infects glial cells and causes progressive multifocal leukoencephalopathy (PML), a demyelinating disease of the brain, in immunosuppressed individuals. The extent of JCV infection of neurons is unclear. We determined the prevalence and pattern of JCV infection in gray matter (GM) by immunostaining in archival brain samples of 49 PML patients and 109 control subjects. Among PML patients, 96% had demyelinating lesions in white matter and at the gray-white junction (GWJ); 57% had them in the GM. Most JCV-infected cells in GWJ and GM were glia, but JCV also infected neurons in PML lesions at the GWJ of 54% and GM of 50% patients and in GM outside areas of demyelination in 11% of patients. The JCV regulatory T antigen (Ag) was expressed more frequently in cortical neurons than the VP1 capsid protein. None of the control subjects without PML had any cells expressing JCV proteins. Thus, the cerebral cortex often harbors demyelinating lesions of PML, and JCV infection of cortical neurons is frequent in PML patients. The predominance of T Ag over VP1 expression suggests a restrictive infection in neurons. These results indicate that JCV infection of cerebral cortical neurons is a previously underappreciated component of PML pathogenesis.